Prestressed beam system due to the addition of a long-span beam in building infrastructure - Debora Evlin; I Nengah Sinarta (Journal of Infrastructure Planning and Engineering, 2022)
Prestressed concrete is the perfect composite consisting of high-strength concrete and strands with reinforcement with high yield strength Prestressed concrete beam is one of the concrete innovations that have been used in many constructions. The advantage of prestressed concrete particularly using the post-tensioning method, in designing and applying prestressed concrete beam for the building is that the tensioning can be carried out in stages, for all tendons in a member, or some of them Prestressed concrete beam using post-tensioning method can be an alternative to increase the span of the building when removing the existing column in the center of the building is required. In this paper, the use of prestressed concrete beam will be designed in Nyitdah Hospital-Tabanan, Bali. The prestressed beam is designed with 60/90 cm dimension and 1 tendon unit with 12 strands unit. Based on the design and result, the prestressed beam can be used as the alternative to increase spans in a building room of the Nyitdah hospital.